Thermodynamic basis of twin-related variant pair in high strength low alloy steel. (September 2019) - Wu, B.B.; Wang, Z.Q.; Yu, Y.S.; Wang, X.L.; Shang, C.J.; Misra, R.D.K.
Abstract: We elucidated here the mechanism of formation of twin-related V1/V2 variant pair from the perspective of thermodynamics. It was observed that the low cooling rate and phase transformation near Ms temperature contribute to produce more V1/V2 variant pairs. The reason why the content of V1/V2 variant pairs in the lath bainite is higher than that of martensite is the diffusion of carbon, which the local carbon enrichment promotes the increase of the content of V1/V2 variant pairs. The microstructure of high-hardenability steel at low cooling rates is mainly lath bainite with a higher content of V1/V2 variant pairs. Graphical abstract: Unlabelled Image